Developing Financial Risk Strategy Decisions for Construction Projects from Perspective of the Project Owner - Budi Dharma; Dara Citra Pratiwi (Journal of Management and Business Innovations, 2020)
Project funding risks can arise from sources of funds, which mostly come from equity and bonds. In addition, the impact is in the form of cost overruns and delays in project completion. Identification of the risk probability that may occur is the first step in controlling the achievement of targets as expected by measuring each risk level that may occur and mapping each level of risk. Then proceed with the mitigation process and monitoring methods. The proper mitigation will undoubtedly bring benefits to the project owner. Hence, the need arises for Developing Financial Risk Strategy Decisions for Construction projects from the project owner's perspective. We use Risk Index and AHP (Analytical Hierarchy Process) to get decision strategy in financial risk.Keywords: AHP (Analytical Hierarchy Process), risk index, risk management